2021
DOI: 10.1002/hon.2895
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of circ_0012152 inhibits proliferation and induces apoptosis in acute myeloid leukemia cells through the miR‐625‐5p/SOX12 axis

Abstract: Acute myeloid leukemia (AML) is a highly heterogeneous disease featured by a clonal proliferation derived from primitive hematopoietic stem/progenitor cells. Circular RNAs (circRNAs) have been identified as crucial regulators in the progression of various cancers, including AML. However, the molecular mechanism of AML is still not definite. This study aimed to explore the influences of circ_0012152 on cell development in AML cells and the underlying regulatory mechanism. The expression of circ_0012152, microRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Research has indicated that after SOX12 knockdown, β -catenin mRNA, and protein levels are dramatically reduced, and TCF/Wnt activity is reduced, which leads to G1 phase cell cycle arrest and decreased cell colonies, indicating that SOX12 may regulate β -catenin expression to interfere with the TCF/Wnt pathway and participate in leukemia progression [ 15 ]. SOX12 is significantly highly expressed in AML cells, and miR-625-5p targets SOX12 directly to suppress AML cell growth and apoptosis [ 45 ]. Additionally, SOX12 knockdown inhibits AML cell proliferation via repressing Wnt/ β -catenin axis activity, whereas miR-489-3p can reverse the effect of SOX12 [ 44 ], which is similar to our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that after SOX12 knockdown, β -catenin mRNA, and protein levels are dramatically reduced, and TCF/Wnt activity is reduced, which leads to G1 phase cell cycle arrest and decreased cell colonies, indicating that SOX12 may regulate β -catenin expression to interfere with the TCF/Wnt pathway and participate in leukemia progression [ 15 ]. SOX12 is significantly highly expressed in AML cells, and miR-625-5p targets SOX12 directly to suppress AML cell growth and apoptosis [ 45 ]. Additionally, SOX12 knockdown inhibits AML cell proliferation via repressing Wnt/ β -catenin axis activity, whereas miR-489-3p can reverse the effect of SOX12 [ 44 ], which is similar to our observations.…”
Section: Discussionmentioning
confidence: 99%
“…In malignant pleural mesothelioma (MPM) (34,35) and thyroid cancer (TC) (36,37), miR-625 was found to be upregulated. It is downregulated in bladder cancer (38), nasopharyngeal carcinoma (NPC) (39), lung cancer (40)(41)(42)(43)(44)(45)(46), HCC (47), cervical cancer (CC) (48,49), osteosarcoma (50), melanoma (51)(52)(53)(54), laryngeal squamous cell carcinoma (LSCC) (55), acute myeloid leukemia (AML) (56), BC (57)(58)(59), glioma (60,61), esophageal cancer (EC) (62)(63)(64), clear cell renal cell carcinoma (65), GC (66)(67)(68)(69)(70), and pancreatic ductal adenocarcinoma (PDAC) (71). In colorectal cancer (CRC), the expression of miR-625 seems to vary, being either high or low.…”
Section: Mir-625 In Cancers Aberrant Expression Of Mir-625 In Cancersmentioning
confidence: 99%
“…Gain-of-function assays suggested that after transfection with miR-625-5p, the proliferation of U937 and HL60 cells was significantly reduced, whereas the miR-625-5p + SOX12 group had the opposite pattern. Therefore, miR-625-5p can regulate AML cell growth by targeting SOX12 (56). Ma et al also pointed out that miR-625 participated in the occurrence and development of AML through Wnt/β-catenin signaling (110).…”
Section: Acute Myeloid Leukemia (Aml)mentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of circ_0002483 inhibited AML cell proliferation and facilitated cell cycle arrest and apoptosis by regulating miR-758-3p/MYC axis ( Xiao et al, 2021 ) ( Figure 4A ). Shang et al found that the expression of circ_0012152 was enhanced in AML tissues and cells, circ_0012152 knockdown inhibited cell proliferation, induced cell apoptosis and facilitated death in AML cells by regulating miR-625-5p/SOX12 axis ( Shang et al, 2021 ) ( Figure 4A ). In addition, Lux et al reported that circBCL11B exclusively expressed in AML patients but not detected in healthy hematopoietic stem and progenitor cell samples, inhibition of circBCL11B suppressed leukemic cell proliferation and led to enhanced cell death of leukemic cells ( Lux et al, 2021 ).…”
Section: Circrnas Regulte Cell Differentiation Cell Cycle Progression...mentioning
confidence: 99%